Análise de aderência de ferramentas de software para apoiar o controle estatístico de processos de software - ABREU, Diego Oliveira (2020)
Statistical Process Control is a process that is present in quality models as CMMI-DEV and MR-MPS-SW, in higher maturity levels. It has as objective, use the process of Measurement, which is also a process present in the mentioned quality models, but in lower maturity levels, to control measured processes and to provide a continuous improvement to the processes. This Term paper proposes the using of software tools available in the industry, to implement the Statistical Process Control following the quality model MR-MPS-SW. Thereby, a guide is proposed for the implementation of the Statistical Process Control, so that the software tools can be used to attend the MR-MPS-SW demands.